IMPROVING TEACHING PRACTICUM: SUGGESTIONS FROM THE ANALYSIS OF FOREIGN LANGUAGE TEACHER EDUCATION CURRICULA - Anh, Ha Le Kim (VNU Journal of Foreign Studies; Vol 35 No 2DO - 10.25073/2525-2445/vnufs.4354, 2019)
Teaching practicum is an important component of a foreign language teacher education program, which helps future teachers to learn and develop pedagogical competence in a real-life context. Within the scope of this article, we focus on analyzing the foreign language teacher education curricula of 9 universities in Vietnam, and offer our recommendations for improving foreign language teacher education in general and English teaching practicum in particular at the University of Languages and International Studies, Vietnam National University, Hanoi.